(untitled) (Scientific journal of the Fergana State University, 2023)
The article is comprehensive and the research examines the social factors behind labor migration, including the unemployment rate and people’s housing needs as the main factors that shape their labor migration. Also, in this article, the role of cocktail migration in the well-being of the population, its impact on economic development, is analyzed using the research data and the results of sociological research conducted by the republican public opinion research center "Social Opinion" conclusions and suggestions are presented.